Analysis of Lecturer Performance With Job Satisfaction as A Mediation Variable at Nazhatut Thullab Al-Muafa University, Sampang - Maksum, Muhammad Iqbal; Nur, Dhani Ichsanuddin; Swasti, Ika Korika (PT. Maju Malaqbi Makkarana, 2025)
This study aims to analyze the influence of leadership and work motivation on lecturer performance, both directly and indirectly through job satisfaction as a mediating variable at Nazhatut Thullab Al-Muafa University, Sampang. This study used a quantitative approach with the SEM-PLS method. The study population was all 66 permanent and non-permanent lecturers, using a census method (total sampling). The primary theory underlying this study is Goal Setting Theory. This study used a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results show that leadership can contribute to lecturer performance. Work motivation contributes to lecturer performance. Leadership contributes to lecturer performance through job satisfaction. Similarly, motivation contributes to lecturer performance through job satisfaction. These findings theoretically sharpen and expand the concepts discussed, and practically can serve as guidelines for Nazhatut Thullab Al-Muafa University, Sampang, in improving lecturer performance, evaluating, and driving institutional progress.